Comparing Early Postoperative Maternal Complications in Elective and Emergency Cesarean Sections - Mostafayi Mehrnush; behzad Imani; Zandi Shirdel; Soghra Rabie (Mashhad University of Medical Sciences, 2020)
Background & aim: Scientifically, cesarean section (C-section) should be performed in case of emergency; however, the frequency of C-sections that are elective and without medical indication is high. This study aimed to compare the early postoperative maternal complications of elective and emergency C-sections. Methods: This descriptive study was carried out on a total of 120 patients undergoing elective and emergency C-sections at Fatemieh Hospital in Hamadan, Iran, between May to July 2019. The study participants were selected through convenient sampling from two groups of elective (N=60) and emergency C-sections (N=60). The data were collected using self-structured questionnaire on early maternal complications and were analyzed by SPSS software (version 23) using Chi-square and independent t-test. Results: A significant difference was observed between the two groups regarding the mean amount of intraoperative bleeding (P<0.05). During 24 h after the surgery, the emergency cesarean group received significantly more analgesics than the elective cesarean group (P<0.05). However, the two groups were not significantly different in terms of operative time, ileus, pain 6 h after surgery, and incidence of infection (P>0.05). Conclusion: The incidence rates of some maternal complications were relatively higher in the emergency C-section than those reported for elective C-section. Therefore, in order to prevent postoperative complications related to emergency C-section, gynecologists should be encouraged to decide timely for cesarean section if there is a particular indication. Also, it is required to provide considerable care to decrease the rate of maternal morbidity and mortality in these cases.